Understanding Complex Relationships between Teachers and Parents - Deslandes, Rollande; Barma, Sylvie; Morin, Lucille (International Journal about Parents in Education, 2023)
Collaborative relationships between school and families are increasingly put forward as a means to promote student success and persistence. This collaborative work sometimes creates tensions and misunderstandings (Ravn, 2005) that can exacerbate divisions of power and reproduce inequalities (e.g., Crozier, 2000; Lareau, 2011; Vincent 2000). The main purpose of this study is to identify the areas of tensions and inner contradictions that emerge in the teacher-parent relationships in order to guide them while engaging in individual and collective transformation processes. Relying on Hoover-Dempsey et al.’s proposed model (2010), we conducted in-depth interviews with volunteered elementary and secondary teachers. Salient findings are discussed in light of the cultural-historical activity theory (CHAT) (Engeström, 2015). These include mainly issues of trust versus control when it comes to choosing communication tools and issues related to the hierarchical status and power inside and outside the school when it comes to the redistribution of actions among the school community members. As a promising research and intervention avenue, the authors suggest to apply the Change Laboratory method (Virkkunen & Newnham, 2013) anchored in CHAT and that uses mirror data to reflect upon and foster transformative processes, hence, relationships between teachers and parents.